Disorder-specific versus transdiagnostic and clinician-guided versus self-guided treatment for major depressive disorder and comorbid anxiety disorders: A randomized controlled trial. (October 2015) - Titov, N.; Dear, B.F.; Staples, L.G.; Terides, M.D.; Karin, E.; Sheehan, J.; Johnston, L.; Gandy, M.; Fogliati, V.J.; Wootton, B.M.; McEvoy, P.M.
Highlights: Study compared disorder-specific and transdiagnostic treatment approaches. Study also compared clinician-guided and self-guided treatment approaches. Study is 1 of 4 related randomised controlled trials examining these issues. Study focused on major depressive disorder and comorbid anxiety disorders. No marked differences were observed between the treatment approaches. Abstract: Disorder-specific cognitive behavior therapy (DS-CBT) is effective at treating major depressive disorder (MDD) while transdiagnostic CBT (TD-CBT) addresses both principal and comorbid disorders by targeting underlying and common symptoms. The relative benefits of these two models of therapy have not been determined. Participants with MDD ( n  = 290) were randomly allocated to receive an internet delivered TD-CBT or DS-CBT intervention delivered in either clinician-guided (CG-CBT) or self-guided (SG-CBT) formats. Large reductions in symptoms of MDD (Cohen's d  ≥ 1.44; avg. reduction ≥ 45%) and moderate-to-large reductions in symptoms of comorbid generalised anxiety disorder (Cohen's d  ≥ 1.08; avg. reduction ≥ 43%), social anxiety disorder (Cohen's d  ≥ 0.65; avg. reduction ≥ 29%) and panic disorder (Cohen's d  ≥ 0.45; avg. reduction ≥ 31%) were found. No marked or consistent differences were observed across the four conditions, highlighting the efficacy of different forms of CBT at treating MDD and comorbid disorders.